The Economization of Diversity. Issue 4 (October 2019) - Thomas, James M.
Through a case study of an ongoing diversity initiative at Diversity University (DU), a public, flagship university in the U.S. South, the author's research advances understanding of the discursive relationship between neoliberalism and contemporary racial ideology. As part of a larger ethnographic project, the author draws on more than ten years worth of diversity discourse at DU to illuminate diversity's economization : the process whereby specific formations of economic values, practices, and metrics are extended toward diversity as justification for DU's efforts. The analysis responds to three questions: (1) How is diversity economized by the organization? (2) How is this economization articulated through organizational discourse on diversity? and (3) How does the economization of diversity potentially reconfigure race and racial subjectivities? The findings reveal three interrelated processes that facilitate diversity's economization: diversity as investment, diversity metrics, and diversity as affective labor . Together these processes congeal and convert multicultural principles and practices into economic ones. Consequently, diversity's economization recasts nonwhite racial subjectivity as human capital for DU and its white publics, minimizing and entrenching existing racial inequality in the process.